The Implementation of Small-Sided Games Training to Improve Passing and Controlling Skills at SSB Tunas Inti Jaya U-12, Lengkong Village, Kuningan Regency - Muhammad Rizki Putra Pratama Rizki; Budi (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study analyzes the effectiveness of the Small-Sided Games (SSG) method in improving passing and control skills among child soccer players (U-12). Using a quantitative method with a One Group Pretest-Posttest Design, the sample consists of 20 players from SSB Tunas Inti Jaya selected through purposive sampling. The research instrument shows a validity of 0.65 and a reliability of 0.77. The results of the normality test using Chi-square indicate a normal distribution in the pretest and posttest data. The Paired Sample t-test shows a significant improvement with a mean difference of +2.3 from the pretest score (3.05) to the posttest score (5.35). This study demonstrates that SSG training is effective in enhancing passing and control skills in U-12 players after 12 training sessions, making it an important training program for the development of basic soccer techniques in early childhood.